Mapping the experience and use of traditional healing in Northern Norway. Among conventional health care providers, users and traditional healers - Larsen, Anette Iren Langås (UiT The Arctic University of Norway, 2018)
The paper I is not available in Munin. Paper I: Larsen, A.L., Hamran, T. & Foss, N. (2014). Mellom profesjonell og folkelig kunnskap: En kvalitativ studie av helsepersonell sin kunnskap om og håndtering av «læsing» i en norsk-samisk kommune. Available in Vård i Norden, 34(4), 53-57. The aim of this research project was to improve the knowledge of the people in Northern Norway (the Sami, Kven, and Norwegians) understanding of health, including the use of traditional healing. We conducted 60 semi-structured interviews and 7 focus group interviews. The participants were health personnel, healers, and users of traditional healing. Both the Sami and Norwegians often used traditional healing. The users seldom reflected on the reasons for using healing as this was a natural part of their culture. In cases of illness, traditional healing was used in combination with conventional medical treatment. The users wanted the health personnel to have knowledge of the use of traditional healing to help facilitate this use for the users when they were admitted in hospitals or nursing homes. In cases of illness, the social network functioned as a collective working system and a safety net that provided practical help and support for the patients and their families. The healers explained their healing ability as a divine power that worked within them. The healers combine Christian prayers and Sami rituals with information from conventional medicine (diagnosis and medical test results) when conducting the healing rituals. The older healers trained the younger candidates. The healers had to be mentally strong, able to arouse trust, and trustworthy. The health personnel in our research project had no education in traditional healing and culture. Nevertheless, many of them conducted traditional healing including the use of familiar rituals upon the patients´ request. The health personnel claimed that this provided the users with more culturally sensitive health care services, even though the use was never documented in the ...